Patterns and Gaps Identified in a Systematic Review of the Hepatitis C Virus Care Continuum in Studies among People Who Use Drugs - Jordan, Ashly E.; Perlman, David C.; Reed, Jennifer; Smith, Daniel J.; Hagan, Holly (Frontiers in Public Health, 2017)
Introduction Systematic reviews are useful for synthesizing data on various health conditions and for identifying gaps in available data. In the US, the main risk group for hepatitis C virus (HCV) infection is people who use drugs (PWUD); as a group, PWUD have the highest prevalence of chronic HCV. While the care continuum construct has been increasingly applied to studies of HCV care among PWUD, what constitutes the steps in an HCV care continuum is not standardized. We sought to examine the range of HCV care continuum outcomes that studies reported on, to identify gaps in the literature, and to develop strategies that allowed for valuable syntheses of care continuum data. Methods We conducted searches of electronic databases for published literature. Reports were eligible if they provided original data from 1990 to 2016 from the US, presented data on one or more HCV care continuum outcomes, and provided outcome data on PWUD as a distinct group. Results A total of 313 full-text reports were assessed for eligibility. Of 212 potentially eligible reports, 32 (15.1%) did not present outcomes for PWUD separately from those who were non-PWUD. Among 101 eligible reports, a total of 166 care continuum outcomes were extracted; outcomes could be grouped into three categories that represent the HCV care continuum: testing (39.8%, n = 66/166); linkage to care (16.9%, n = 28/166); and treatment (43.4%, n = 72/166). Seventy-four reports (73.3%, n = 74/101) presented data on only one step. Linkage to care occurred variably after only antibody, or after antibody and viral load (VL) testing. Six (5.9%, n = 6/101) reports presented data on all three steps. Conclusion Reports examined a variety of HCV care continuum outcomes that could be grouped into the three steps of testing, linkage to care, and treatment. The application of this care continuum model would facilitate subsequent data synthesis for program comparison and public health evaluation. Given the two-step nature of HCV testing, analyses also need to account for variation in whether linkage to care occurred after antibody testing or after sequential antibody and VL testing. Additional data are needed on the progression of PWUD through the entire care continuum.